2015 year in review: state advanced energy legislation - Hoffer, Katherine Heriot, author; Cook, Jeff, author; Edmonds, Chris, author; Culkin, Jane, author; Smith, Alison, author; Lyng, Jeff, author; Plant, Tom, author; Kelly, Ian, author; Brunmeier, Ben, author; Center for the New Energy Economy, publisher (Colorado State University. Libraries, 2016)
With the 2016 legislative sessions about to begin, the Center for the New Energy Economy (CNEE) takes a look back at advanced energy legislation enacted by U.S. states in 2015.
Keywords: Energy policy; Renewable energy sources -- Law and legislation -- United States